Public relations education - Betsie Ferreira (Communicare)
In this article the question is posed to what extent the prescriptive model for public relations education formulated by the International Public Relations Association (IPRA) can be accepted as a role model for South Africa. This model, known as The Wheel of Education, was proposed by IPRA to suggest generally accepted educational standards. The model takes the form of a recommended curriculum accompanied by a set of general re~ommendations pertaining to education and research. In this article, an attempt is made to test the validity of this model by reviewing it in terms of both international and South African literature. It is suggested that the model has international validity but lacks sufficient emphasis on international public relations. It is also suggested that the model cannot be applied strictly as a blueprint for public relations education in South Africa, but needs to be adapted to the development needs of this country.